Estimation of powerquality in distribution system using fuzzy logic theory - Adeel Saleem; Kholiddinov Ilkhombek Khosiljonovich; Kholiddinova Mashkhurakhon Mutalibjon Qizi; Komolddinov Sokhib; Sharobiddinov MirzohidShakhobiddin Ugli; Soliev Sokhibjon Obidovich (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
There are several methods are used to calculate the power quality indicators. These objectives are now served by the most recent soft computing theories, such as neural networks, fuzzy time  series, fuzzy logic theory, and other techniques. The fuzzy logic theory is one of the methods used to calculate the power quality indicators for the distribution electric network in this paper. It resolves the issue of forecasting the voltage values on distribution electrical networks' buses and enhances the quality of electricity in the face of fluctuating consumer loads and uncertainty. This paper proposed a device that has the ability for monitoring the quality of electricity domestically which leads to getting rid of many problems such as voltage deviations and asymmetrical  faults. The fuzzy logic theory is implemented to develop the algorithm for this purpose. The actual data is recorded at the distribution transformer and implement the fuzzy logic theory by using a mathematical model as well as the simulation on MATLAB for optimizing the power quality indicators with the help of fuzzy logic theory and results are discussed at the end of the paper.